The grizzlies - Thomas, Theodore; Palattella, Lisa (WQED/Pittsburg : National Geographic Society, 1987)
Tells the history of the grizzly bear, showing them in the wild and with an animal trainer. Uses old footage and photographs to show how they were hunted in the past
Keywords: Grizzly bear